Inherited thrombophilia in young Indian adults presenting with thrombotic vascular events - Sahay, Ravindranath; Bhate, Priya; Borikar, Nikhil A. (International Journal of Research in Medical Sciences, 2017)
Background: There is limited Indian data available regarding inherited thrombophilias. This study was to determine the prevalence of inherited thrombophilias in young Indian patients presenting with thrombotic events. Methods: This study was done at a tertiary hospital in Western India over a period of 20 months. Epidemiological, clinical and laboratory data was recorded of all consecutive patients aged 16 to 45 admitted with arterial and venous thrombotic vascular events. Blood samples for the thrombophilia profile were sent. Data was tabulated and analyzed using microsoft excel and graph pad software. Results: 49 patients aged 15 to 45 years, admitted with thrombotic vascular events a period of 20 months were included. 26 (53.1%) were male. The mean age was 22.2±7 years. 20 (40.8%) patients; 10 (38.5%) males and 10 (43.5%) females had at least one thrombophilia. The commonest thrombophilia in both arterial and venous thrombotic events was hyperhomocysteinemia. Conclusions: Young patients with thrombotic vascular events should be tested for thrombophilias since they are an important risk factor in this subset of patients.